EXPERIMENTAL STUDY OF THE INLET FLOW IN A NON-PREMIXED COMBUSTION CHAMBER - Trevisan, B. P.; Dourado, W. M. C. (Revista de Engenharia Térmica, 2020)
The evaluation, validation and development of the models used in computation fluid dynamics requires the availability of experimental data for which the boundary conditions, especially the conditions of the inlet flow, are well defined. Laser diagnostics techniques provide experimental data used in computational fluid dynamics and are a powerful tool for measurements of the mean properties and fluctuations of the turbulent flow because they are non-intrusive methods, with high repetition rate and high spatial and temporal resolution. Therefore, in the present work an experimental study of the inlet flow (inert and combusting flows) in a non-premixed combustion chamber is presented. The velocity measurements were carried out using a laser Doppler velocimeter at the entrance region of the combustion chamber. An asymmetry on the mean flow and an increase on the total velocity fluctuations with the increase of the equivalence ratio was observed. The major effect on the increase of the equivalence ratio was a presence of a coherent movement on large scales associated to the flame brush dynamics.